Total Parathyroidectomy with Presternal Intramuscular Autotransplantation in Renal Patients: A Prospective Study of 66 Patients. (9th February 2012) - Santos, R. O.; Ohe, M. N; Carvalho, A. B.; Neves, M. C.; Kunii, I.; Lazaretti-Castro, M.; Abrahão, M.; Cervantes, O.; Vieira, J. G. H.
Abstract : Surgical treatment of secondary (SHPT) and tertiary hyperparathyroidism (THPT) may involve various surgical approaches. The aim of this paper was to evaluate presternal intramuscular autotransplantation of parathyroid tissue as a surgical option in SHPT and THPT treatment. 66 patients with renal chronic disease underwent surgery from April 2000 to April 2005 at Universidade Federal São Paulo, Brazil. There were 38 SHPT patients (24 women/14 men), mean age of 39.yrs (range: 14–58), and 28 THPT patients (14 women/14 men), mean age of 43.4 yrs (range: 24–62). Postoperative average followup was 42.9 months (range: 12–96). Postoperative intact PTH increased throughout followup from 73.5 pg/mL to 133 pg/mL on average from 1st to the 5th year, respectively, in SHPT and from 54.9 pg/mL to 94.7 pg/mL on average from 1st to 5th year, respectively, in THPT group. Definitive hypoparathyroidism was observed in 4 (6.06%) patients and graft-dependent recurrence in 6 (9.09%). Presternal intramuscular autotransplantation of parathyroid tissue is a feasible and safe surgical option in SHPT and THPT treatment.